PERAN PROGRAM BAZNAS MICROFONANCE DALAM MENGURANGI KEMISKINAN DI LOMBOK BARAT - Muhammad Daud; Ahmad Amir Aziz; Zulpawati Zulpawati (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
Poverty has become a social problem in West Nusa Tenggara, especially in West Lombok, after the 2018 earthquake. Various efforts by the government and the private sector to reduce poverty are still relatively high. This study aims to describe the types of Village BAZNAS Microfinance (BMD) empowerment, the role of the Village BAZNAS @@Microfinance (BMD) program in reducing poverty and an overview of the aspects of maqas}id shari'ah. The research method used is descriptive qualitative, describing field phenomena by observing, interviewing, and documenting. As for analyzing the research data using data reduction, data presentation, and conclusions or verification. The results of this study are empowerment through the Gunungsari Village BAZNAS Microfinance (BMD) program, there are two types, the first is consumptive distribution, and the second is a creative productive distribution where mustahik or beneficiaries are grouped by type of business and are given interest-free financing. Meanwhile, the role of the Gunungsari Village BAZNAS Microfinance (BMD) program in reducing poverty is to conduct assessments for fostered points, provide financing, and provide assistance with the Participatory Action Research (PAR) approach. Mentoring activities include spiritual strengthening, adding insight, and product development. Referring to the fulfillment of maqas}}id shari'ah there are five aspects of fulfilling the first maintenance of religion, second maintenance of the soul, third maintenance of the mind, fourth maintenance of offspring, and fifth maintenance of the property.